ANALYSIS OF THE STEELS THERMOPHYSICAL CHARACTERISTICS WITH THE PUФOSE OF APPLICATION FOR SOLVING OF NON-LINEAR PROBLEMS OF HEATING THEORY - V. I. Timoshpolski; S. M. Kabishov; E. V. Kalinevich; R. B. Vais (Литьë и металлургия)
The article is dedicated to analysis of the existing calculation methods of thermalphysic characteristics of steel of different chemical composition depending on temperature and development of new methods for determination of actual heat capacity of the carbon types of steel.